A Critical Review on the Book After the Prophet - Yazdan Farrokhi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The great Prophet of Islam (PBUH) always invited his followers to unity based on Quranic concepts, but the new Umma of the Islamic Foundation, shortly after the death of the Prophet (PBUH), broke away from those teachings, and one of the consequences was the killing of Muslims by each other. The roots of this disconnection have always been considered by researchers and much research has been done in this field. The aim of this article is to critically evaluate the book "After the Prophet" in which the author has tried to clarify various aspects of the issue in line with previous research and in a different way. To what extent has the method of advancing and conducting this research been successful in explaining the research problem? It seems that the author, while observing the principles of historical research, has used areas such as psychology, cinema, fiction, anthropology and has studied the historical roots of the current crisis of Muslims in the Middle East, especially in Iraq. The result of the present article, which has been done by descriptive-analytical method, shows that the importance of the book under review is, above all, in the interdisciplinary approach and the author's new way of expressing the research problem, which has created a new effect. However, some views have been raised and the methods of advancing the research need to be reviewed.